20th-century climate change inferred from four long-term point observations of seasonal mass balance - Huss, Matthias; id_orcid:0 000-0002-2377-6923; Bauder, Andreas; id_orcid:0 000-0001-7197-7706 (Annals of Glaciology, 2009)
ISSN:0260-3055 ISSN:1727-5644